2009
DOI: 10.4319/lo.2010.55.1.0420
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus inputs control phytoplankton growth in eutrophic Lake Taihu, China

Abstract: Lake Taihu (Taihu) is the third largest freshwater lake in China and an important drinking water, fishing, and tourism resource for Jiangsu Province. Recent toxic cyanobacterial blooms caused by excessive human nutrient loading have focused attention on arresting blooms and restoring the lake to acceptable water quality conditions by reducing nutrient inputs. Field sampling and in situ nutrient enrichment bioassays were conducted to determine seasonal patterns of nutrient limitation and nutrient thresholds for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
422
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 892 publications
(494 citation statements)
references
References 45 publications
37
422
0
9
Order By: Relevance
“…The most common way of adding nutrient is adding a finite supply of dissolved nutrients as the setting concentrations at the beginning of the experiment and adding no more nutrients during the process of phytoplankton incubation (Domingues et al 2011;Ma et al 2015a, b;Paerl et al 2011;Xu et al 2010Xu et al , 2015. However, there are some problems with this approach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common way of adding nutrient is adding a finite supply of dissolved nutrients as the setting concentrations at the beginning of the experiment and adding no more nutrients during the process of phytoplankton incubation (Domingues et al 2011;Ma et al 2015a, b;Paerl et al 2011;Xu et al 2010Xu et al , 2015. However, there are some problems with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient threshold is defined as the critical levels of N and P that control an abrupt change or regime shift such as sudden and protracted dominance by phytoplankton (Xu et al 2014). Previous studies have shown that eutrophication thresholds of total phosphorus (TP) for freshwaters are from 0.02 to 0.10 mg P L −1 and of total nitrogen (TN) are from 0.50 to 1.00 mg N L −1 (Xu et al 2010). Abundant evidence has proven that understanding and applying ecological thresholds is the key to successful environmental management (Groffman et al 2006).…”
Section: Responsible Editor: Thomas Heinmentioning
confidence: 99%
See 3 more Smart Citations